TBIO-30. MOLECULAR LANDSCAPE AND CLINICAL CORRELATIONS OF CNS SARCOMAS. Issue 2 (22nd June 2018) - Fonseca, Adriana; Ho, Ben; Torchia, Jonathon; Leary, Sarah; Lu, Mei; Sommers, Gino; Gupta, Abha; Grant, Ronald; Norman, Joe; Lafay-Cousin, Lucie; Hawkins, Cynthia; Bartels, Ute; et al.
Abstract: BACKGROUND: Central nervous system (CNS) sarcomas are rare mesenchymal tumors accounting for less than 0.2% of intracranial (IC) tumors. Due to their rarity molecular insights they may be misdiagnosed as embryonal brain tumors, thus best clinical approach has been lacking METHODS: 17 IC and 4 extracranial (EC) sarcomas were examined using methylation profiles and RNASeq analyses to define molecular features and clinicopathologic correlations. RESULTS: CNS sarcomas segregate into 3 sub-groups; the majority exhibited CIC (n=17) or EWS (n=9) fusions, a small subset (n=3) has no defining alteration. All IC EC sarcomas with the same molecular alterations indicating they were not distinct brain tumor types. Median age was 4.25-yrs, 10.6-yrs and 14-yrs for the CIC, EWS and undifferentiated subgroup respectively. The 5-yr PFS was 33%, 75% and 100% and OS was 49%, 83% and 100% for the CIC, EWS and undifferentiated group respectively. CONCLUSION: IC and EC sarcomas represent a common molecular diseases, and should be treated using similar approaches.